OP0265-HPR FACTORS ASSOCIATED WITH MEETING WORK DEMANDS FOR INDIVIDUALS WITH RHEUMATIC DISEASES. (2nd June 2020) - Connolly, D.; Fitzpatrick, C.; O'toole, L.; O'shea, F.; Doran, M.
Abstract : Background: Almost 65% of individuals with rheumatic diseases have severe fatigue with the majority of these reporting difficulties in work leading to absenteeism and early retirement. However, there is a lack of research investigating how different types of fatigue impact on work ability. Objectives: To identify the prevalence of different types of fatigue and explore the association between different types of fatigue and various demands involved in work Methods: A cross-sectional study was carried out with 234 individuals with rheumatic diseases currently in employment. Study measures examined demographics, different types of fatigue (general, physical reduced activity, reduced motivation and mental), ability to meet work demands, disease activity and quality of life. Results: The majority of participants were female (70%), had rheumatoid arthritis (42.7%), were between 41-50 years (30.3%) and worked full-time (70%). One hundred and twenty-eight participants (55%) had severe fatigue. Physical fatigue was the most prevalent category of fatigue (Table 1 ). Participants reported managing 50% of their work demands with physical demands being the most challenging (Table 1 ). All types of fatigue were significantly associated with the total WRF score (Table 2 ). Mental fatigue had the strongest association with the total WRF score (r=0.53, p<0.001). On examining the impact of different types of fatigue on meeting work demands, mental fatigue was the most significant predictor of difficulty meeting work demands (β =1.6, SE=0.37, p<0.001) Conclusion: Fatigue interferes with many aspects of work performance. However, this study identifies that mental fatigue is the greatest predictor of difficulty in managing work. Self-management interventions focusing on mental fatigue and work ability are required for individuals with rheumatic diseases to manage the demands of their work. Disclosure of Interests: None declared